2015
DOI: 10.1159/000398799
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin 1 Modulates Monocyte Properties to Suppress Intestinal Mucosal Inflammation

Abstract: Monocytes (Mos) play an important role in the pathogenesis of intestinal mucosal inflammation. This study aims to investigate the mechanism by which the intestinal epithelial cell-derived thrombospondin 1 (TSP1) modulates Mo properties and regulates intestinal inflammatory responses. In this study, the production of TSP1 by intestinal epithelial cells was evaluated by quantitative real-time PCR and Western blotting. The properties of Mos were analyzed by flow cytometry. A mouse model of colitis was created to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Importantly, TSP1-primed monocytes upregulated TGFβ levels and successfully inhibited inflammation in the intestine. Since inflammatory bowel disease (IBD) is characterized by chronic inflammation in the intestinal tract and carcinogenesis is promoted by persistent chronic inflammation occurring in IBD, understanding the underlying mechanisms is essential in order to ameliorate inflammation and prevent colorectal cancer [ 76 , 84 ]. However, not all macrophages or monocytes residing in tumors are tumoricidal.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, TSP1-primed monocytes upregulated TGFβ levels and successfully inhibited inflammation in the intestine. Since inflammatory bowel disease (IBD) is characterized by chronic inflammation in the intestinal tract and carcinogenesis is promoted by persistent chronic inflammation occurring in IBD, understanding the underlying mechanisms is essential in order to ameliorate inflammation and prevent colorectal cancer [ 76 , 84 ]. However, not all macrophages or monocytes residing in tumors are tumoricidal.…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers believe that the TSP1 protein promotes the migration of mononuclear cells, which subsequently increases inflammatory Mφ to infiltrate vascular tissues (53). However, TSP1 protein could also inhibit pathogenic inflammation by stabilizing monocytes (21,54). In this study, we found that the TSP1 protein tended to increase obviously with the aggravation of colonic mucosal inflammation in colitis rats.…”
Section: Discussionmentioning
confidence: 45%
“…Among t h e m , t h e T S P 1 p r o t e i n p l a y s a c r i t i c a l r o l e i n immunomodulation (20), but has a controversial effect on regulating MPS-mediated immunity in the colon. Some results in previous studies have suggested that TSP1 could reduce Mφ infiltration and the release of inflammatory cytokines, thereby limiting inflammation (21); however, some studies have found that increased TSP1 could aggravate colonic mucosal injuries though promoting the migration and activation of monocytes (22). Interestingly, our previous study found that the expression of TSP1 in colon was significantly increased in UC, which could increase the inflammation and vascular injuries in colonic mucosa (23).…”
Section: Introductionmentioning
confidence: 89%
“…Early studies examined TSP1 effects on neutrophil oxidative burst and found that TSP1 synergizes with a formylated bacterial peptide to stimulate an oxidative burst response [ 115 , 116 ]. Others identified inhibitory TSP1 functions in NK cells [ 117 , 118 ], dendritic cells [ 119 , 120 , 121 , 122 , 123 ], and monocytes [ 108 , 117 , 124 , 125 , 126 , 127 ]. Functions of TSP1 in other aspects of immune responses include modulation of TLR3-mediated inflammatory signaling in VSMC [ 71 ].…”
Section: Tsp1 and Antitumor Immunitymentioning
confidence: 99%